David Harvey. Consciousness and the urban experience : studies in the history and theory of capitalist urbanization. Baltimore : The Johns Hopkins University Press, 1985. 293 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1986)
DAVID HARVEY. Consciousness and the Urban Experience Studies in the History and Theory of Capitalist Urbanization. The Johns Hopkins University Press, Baltimore, 1985.